Atlas registration for edema-corrected MRI lesion volume in mouse stroke models - Koch, Stefan; Mueller, Susanne; Foddis, Marco; Bienert, Thomas; von Elverfeldt, Dominik; Knab, Felix; Farr, Tracy D.; Bernard, René; Dopatka, Monika; Rex, André; Dirnagl, Ulrich; Harms, Christoph; et al. (SAGE Publications, 2017)
Lesion volume measurements with magnetic resonance imaging are widely used to assess outcome in rodent models of stroke. In this study, we improved a mathematical framework to correct lesion size for edema which is based on manual delineation of the lesion and hemispheres. Furthermore, a novel MATLAB toolbox to register mouse brain MR images to the Allen brain atlas is presented. Its capability to calculate edema-corrected lesion size was compared to the manual approach. Automated image registration performed equally well in in a mouse middle cerebral artery occlusion model (Pearson r=0.976, p=2.265e-11). Information encapsulated in the registration was used to generate maps of edema induced tissue volume changes. These showed discrepancies to simplified tissue models underlying the manual approach. The presented techniques provide biologically more meaningful, voxel-wise biomarkers of vasogenic edema after stroke.